Blastomere morphology, neutral bouyancy salinity, and osmotality as predictive measures. - Denusta, Pastor Jones Tejero
Morphological characteristics of blastomeres, neutral buoynacy salinity and osmolality of the eggs were determined and correlated with egg viability parameters to identify possible measures of egg quality in milkfish 36 to 50 egg samples from twelve batches were analyzed for cell symmetry, size, adhesion, margins, and inclusions. There were no significant correlations between hatch rate and mean score for each blastomere characteristics. However, hatched and unhatched eggs were significantly different for the cell inclusion parameter